Pet Attachment dan Self-Compassion dengan Psychological Well- Being Pada Pemelihara Kucing - Trinanda, Gilang; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research is a quantitative study which aims to determine the relationship between Pet Attachment and Self-Compassion with Psychological Well-Being in cat keepers in the Taman Buaran Indah IV complex. The sampling technique in this research used a Voluntary Sampling technique. Participants in this research were 123 people who kept cats in the Taman Buaran Indah IV complex. Data collection in this study used three scales, namely the Psychological Well-Being scale which has 21 items with a different power of 0.303 â€“ 0.647 and a reliability of 0.846. This research data was analyzed using the enter linear regression method and stepwise linear regression using the JASP (Jeffrey’s Amazing Statistics Program) version 0.18.3.0. The results of this research show that 1) There is no significant relationship between Pet Attachment and Psychological Well-Being (r = 0.144 and p > 0,05); 2) There is a significant relationship between Self-Compassion and Psychological Well-Being (r = 0.436 and p < 0,05); 3) There is a significant relationship between Pet Attachment and Self-Compassion with Psychological Well-Being (R = 0.274 and p < 0,05). This shows that there is a relationship between Pet Attachment and Self-Compassion with Psychological Well-Being among cat keepers in the Taman Buaran Indah IV complex. It is known that the determinant coefficient of R Square is 0.191. This means that Pet Attachment and Self-Compassion together contribute to Psychological Well-Being by 19.1%, thus as much as 80.9% is influenced by factors not researched.